Correction of morphofunctional disturbances arising when modelling Preeclampsia with resveratrol and nicorandil - Elena G. Stupakova; Galina A. Lazareva; Vladimir V. Gureev (Belgorod National Research University, 2018)
Introduction: Preeclampsia is one of the most serious diseases of the second half of pregnancy and is surely amongst the top three causes of maternal mortality. Therefore, the creation of new drugs for preventing and correcting preeclampsia is an urgent task. Methods: In the experiment, an ADMA-like L-NAME-induced model of preeclampsia was reproduced. To assess the emerging morphofunctional disorders, the following parameters were used: blood pressure, endothelial dysfunction coefficient, microcirculation in the placenta, proteinuria, fluid content in the large omentum, concentration of terminal metabolites in the blood plasma, morphological state of the placenta and kidneys and morphometric parameters of the foetus. Results and Discussion: Injection of L-NAME into the animals from the 14th to the 20th day of pregnancy causes disorders: an increase in systolic and diastolic blood pressure by 1.4 and 1.5 times, an increase in proteinuria by 3.3 times and an increase in the fluid content in a large omentum from 45.82 ± 1.82% to 54.73 ± 1.96%, which correspond to disorders due to preeclampsia in pregnant women. There was also a disturbance of endothelial function, as evidenced by an increase in the coefficient of endothelial dysfunction (CED) by 2.9 times. The use of resveratrol leads to a pronounced correction in the changes that occur: a decrease in systolic and diastolic arterial pressure by 1.2 and 1.3 times, a decrease in proteinuria by a factor of 1.9 and a decrease in the fluid content in the large omentum to 50.00 ± 1.25%. The use of nicorandil leads to a pronounced correction in the resulting changes: a decrease in the diastolic blood pressure by 1.14 times, a decrease in proteinuria by a factor of 1.7 and a decrease in the fluid content in the large omentum to 50.57 ± 2.08%. CED decreased 1.7 times. When combining their use with amlodipine, the positive effects increased: systolic and diastolic blood pressure decreased 1.13 and 1.24 times and 1.14 and 1.23 times, respectively, proteinuria decreased 2.7 and 2.3 times, the fluid content in the large omentum was reduced to 44.54 ± 1.80% and 46.73 ± 1.30%. CED decreased 1.7 and 2.3 times. The administration of glibenclamide together with resveratrol and nicorandil removes a significant part of their positive effects. Conclusion: Resveratrol and nicorandil have a significant positive effect in the correction of morphofunctional disorders in animals with ADMA-like preeclampsia. Activation of K+ATP channels plays a significant role in the realisation of their positive effects.